Biostimulasi Perkecambahan Padi Lokal Yang Mengalami Dormansi Melalui Optimalisasi Lama Perendaman Ekstrak Keong Mas Diperkaya Bioaktivator Pgpr - Sri Sudewi; Hasmari Noer; Kasman Jaya; Sulaeman Sulaeman (Jurnal Penelitian Pertanian Terapan, 2025)
Seed dormancy poses a serious challenge when aiming for precise and uniform sowing times in crop cultivation activities. Dormancy can reduce seed viability thus inhibiting germination and early plant growth. The purpose of this study was to test the effectiveness of gold snail extract enriched with PGPR (Plant Growth Promotion Rhizobacteria) bioactivator by optimizing the length of soaking in local rice seeds that experience dormancy. The research was conducted using a Completely Randomized Design (CRD) with 5 treatments of control soaking duration (P0), 12 hours soaking duration (P1), 24 hours (P2), 36 hours (P3) and 48 hours (P4) with 4 replications so that a total of 20 experimental units were obtained. Each experimental unit consisted of 25 local Kamba rice seeds by observing the percentage of germination, vigor index, growth speed, fresh weight, dry weight, root length and pH changes during the fermentation process. The results showed that various treatments of soaking time in gold snail extract enriched with PGPR bioactivator did not provide statistically significant differences in the germination of local rice seeds that experienced dormancy. However, there was an increasing trend in all observation parameters indicating that the viability and vigor of seeds soaked in gold snail extract for 36 hours (P3) were better than the control. pH and temperature observed before and after fermentation, showed conditions that remained optimal. The combination of gold snail extract added with PGPR as a bioactivator is an alternative solution that can accelerate the breaking of dormancy, increase seed viability and vigor as an effort to support more optimal and sustainable early growth of rice plants.